A life threatening intracerebral hemorrhage during pregnancy - Verma, Kamala; Agrawal, Sudesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Intracerebral hemorrhage (ICH) during antenatal period is an infrequent but serious complication. This is a case of elderly woman with pregnancy induced hypertension who developed spontaneous ICH during the thirty five week of pregnancy. She presented to our emergency department with altered sensorium, aphasia and hemiparesis. Intracerebral hemorrhage was diagnosed by MRI. Magnetic resonance angiography failed to identify an aneurysm or arteriovenous malformation. She underwent successful emergency cesarean section. In this case we report the rare Intracerebral hemorrhage (ICH) during antenatal period and its challenging complication, diagnosis and management